Optimalisasi Kader Sebagai Pmo (Petugas Minum Obat) dalam Mengkonsumsi Tablet Fe terhadap Pencegahan Anemia Berbasis Android di wilayah Kerja Puskesmas Simpang Kawat - Lismawati Lismawati; Rica Tri Septinora (Universitas Batanghari Jambi, 2019)
Anemia due to malnutrition of pregnant woman in Indonesia is 70%. On further observation, shows that anemia that suffered by the community due to lake of Fe intake which is can be solved by consume iron regulary. This research is analytic research with quasi experiment design which uses control group which aims to know the difference of hemoglobin level between before and after supervised by cadres as a PMO (Petugas Minum Obat) in consuming Fe tablet agains anemia prevention android based. This research was on July 11 until August 15, 2019. The sample of the study are 30 respondents as the experiment group and 30 respondents as the control group. Begin with the mesurement of respondent’s hemoglobin, then the monitoring given intervention by cadres as the PMO through an android based application. After that, the respondent’s hemoglobin level will be measured again. The data of this research are analized by univariate and bivariate t-test with a = 0,05. The reseach results on unvariate analysis shows the average age af the mother, parity and gestational age are homogeneus with the p-value > 0,05 which means nothing difference on the characteristic of the cadres as the PMO and without cadres as the PMO. Beside that, the result on bivariate analysis shows that p-value < 0,001, so it can be concluded that there is a difference on the level of cadres as the PMO and without cadres as the PMO. With the result, can be interpret that the cadres as the PMO are optimal for enhancement of hemoglobin level in the prevention of anemia on pregnant woman. The efforts made towards the prevention if anemia is to activate all the health worker and the cadres to increase the regularity on consuming the Fe tablet of pregnant woman.